Novel RFID-Based Pose Estimation Using Single Stationary Antenna - Saab, Samer S. (2016)
In this paper, we propose a novel radio-frequency identification (RFID)-based methodology that can estimate the position and orientation of an object. Unlike other RFID-based localization systems, the proposed method employs a single nonsteered stationary antenna and three passive tags mounted on each object. Our scheme is based on power map matching algorithm that is capable in estimating the location and orientation of objects. Unlike conventional power map matching schemes, which create the map from actual measurements, the proposed power map is automatically generated based on a simple mathematical model. The application under consideration is based on two-dimensional (2-D) open spatial environment where the area of each object is no less than a quarter of a square meter with position estimation errors stretching to tens of centimeters. This work provides an alternative and relatively cheap approach for remotely estimating the pose of an object. As a proof of concept, we justify our scheme analytically and provide numerical and experimental data to substantiate the feasibility of our methodology.